CULTURAL ADAPTATION AND RELIABILITY ANALYSIS OF THE EARLY CLINICAL ASSESSMENT OF BALANCE - Ana Paula Bensemann Gontijo; Juliana Maria Pimenta Starling; Graziela Dulce Oliveira; Debora Meier; Marisa Cotta Mancini (Sociedade de Pediatria de São Paulo, 2019)
ABSTRACT Objective: To translate the Early Clinical Assessment of Balance (ECAB), an assessment scale developed specifically for children and adolescents with cerebral palsy into Brazilian Portuguese, evaluate semantic, idiomatic, experiential and conceptual equivalences, and to examine the face validity and the reliability within and between examiners of the Brazilian version. Methods: The following steps were done: translation by two independent translators; synthesis of translations; back translation into English; analysis of back-translations by a multidisciplinary committee and the author of the test to develop the final version of the test; test application training; administration of the translated version of ECAB (videotaped) in 60 children and adolescents with cerebral palsy; intra and inter-examiner reliability assessment. Reability was assessed by intraclass correlation coefficient (CCI). Results: The discrepancies found were related mainly to semantic equivalence and, therefore, there was no need to make cultural adaptations in any of the 13 items on the scale. The rate of agreement was greater than 90% and the reliability of the ECAB-Portuguese total score was excellent both for the intra-rater test (CCI=1.00) and for the inter-rater test (CCI=0.998). Likewise, the reliability evaluation of each of the scale items was also excellent. Conclusions: The translated version of the ECAB into Portuguese provides a tool for the evaluation of the specific balance for children and adolescents with cerebral palsy with different levels of functioning.